2007
DOI: 10.1093/brain/awm027
|View full text |Cite
|
Sign up to set email alerts
|

Heterogeneity of aquaporin-4 autoimmunity and spinal cord lesions in multiple sclerosis in Japanese

Abstract: Opticospinal multiple sclerosis (OSMS) in Asians has similar features to the relapsing-remitting form of neuromyelitis optica (NMO) seen in Westerners. OSMS is suggested to be NMO based on the frequent detection of specific IgG targeting aquaporin-4 (AQP4), designated NMO-IgG. The present study sought to clarify the significance of anti-AQP4 autoimmunity in the whole spectrum of MS. Sera from 113 consecutive Japanese patients with clinically definite MS, based on the Poser criteria, were assayed for anti-AQP4 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

33
314
8
8

Year Published

2007
2007
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 254 publications
(363 citation statements)
references
References 43 publications
33
314
8
8
Order By: Relevance
“…In a recent study 23 , multiple logistic analyses revealed that emergence of the anti-NMO-IgG antibody was positively associated with a higher relapse rate. Thus, this method can be a useful and reliable tool in NMO diagnosis and management in Brazilian patients, in spite of ethnical differences and genetic peculiarities of our population.…”
Section: Discussionmentioning
confidence: 97%
“…In a recent study 23 , multiple logistic analyses revealed that emergence of the anti-NMO-IgG antibody was positively associated with a higher relapse rate. Thus, this method can be a useful and reliable tool in NMO diagnosis and management in Brazilian patients, in spite of ethnical differences and genetic peculiarities of our population.…”
Section: Discussionmentioning
confidence: 97%
“…Cord swelling with focal enhancement was not frequent in non-AM patients. LESCL with selective gray matter on axial images, as is frequent in NMO or opticospinal multiple sclerosis (OSMS) [18,19], were observed in 9 of 15 patients, three of them developed recurrent myelitis. Eccentric large lesions were absent in this group.…”
Section: Discussionmentioning
confidence: 99%
“…Este diagnóstico se establece cuando se cumplen los criterios diagnósticos de NMO establecidos en 1999 y actualizados en 2006. Para ello se debe considerar lo siguiente durante el proceso de evaluación (3,60,61):…”
Section: Diagnósticounclassified
“…estos habitualmente se hallan presentes en títulos bajos. aproximadamente el 50% de los pacientes los presentan de manera ya sea clínica o subclínica; sin embargo, el más importante de los anticuerpos séricos que se buscará es sin duda la presencia de igG-NMO que acercará al diagnóstico clínico del proceso (33,61,62).…”
Section: Diagnósticounclassified